Adolescent peer networks and the moderating role of depressive symptoms on developmental trajectories of cannabis use. (January 2018) - Pollard, Michael S.; Tucker, Joan S.; Green, Harold D.; de la Haye, Kayla; Espelage, Dorothy L.
Abstract: This paper investigated how depressive symptoms moderate the role of peer cannabis use on developmental patterns of individual cannabis use from adolescence to young adulthood, controlling for a broad set of individual and family factors. Data from two sources were analyzed separately: two saturated schools in the National Longitudinal Study of Adolescent to Adult Health Waves I–III ( N  = 1550) covering 1994–2001; and three schools in the CARBIN study, covering 2012–2014. Discrete mixture models identified developmental trajectories of cannabis use in each data source, and logit models linked network and depressive symptom information to the trajectories. Five similar cannabis use trajectories were identified in both datasets: Nonuse, Low, Moderate, Increasing, and High. Peer cannabis use at baseline predicted higher individual cannabis use trajectories, controlling for a wide range of factors. However, the association between peer cannabis use and higher levels of use (Moderate and High) attenuated as the adolescent's level of depressive symptoms increased. Although these results may suggest that depression dampers adolescents' susceptibility to peer influence, these results are also consistent with the notion that depressed adolescents withdraw from their peer groups, distancing them from the initial source of peer influence over time. The resulting isolation may place adolescents at higher risk of adverse outcomes. Highlights: We model longitudinal trajectories of adolescent cannabis use in two data sets, separated by 18 years. We examine peer, family, and individual factors. Peer network marijuana use predicted higher trajectories. Greater levels of depressive symptoms attenuated the role of peer cannabis use. Results suggest depressed adolescents withdraw from peers, may become isolated.